Derivation of an evaluation instrument for judging the quality of ecosystem-based municipal plans. - Novakowski, Erin Nicholas. (University of Ottawa (Canada), 1999)
A basic conundrum associated with evaluating the quality of municipal plans involves the range of interests---public, special, vested---that are either supported or confounded by the plan. Traditionally, comprehensive plan evaluation has proceeded by attaching weights to the evaluation criteria. Yet, such a procedure is inherently flawed since it is self-evident that interested parties are unlikely to fully agree with any weighting scheme that places a lower weight on their own specific priorities. Other factors also challenge the origin and applicability of evaluation criteria that characterize good plans and planning, including the lack of a codified theoretical foundation for both planning in general and planning frameworks in particular (e.g., ecosystem-based planning). These factors make the search for a methodologically-grounded and theoretically-oriented basis for judging plan quality a priority for both planning theory and practice. Currently, the theories of, in or for planning provide little guidance about how to resolve these issues. Using the ecosystem approach to planning as the field of inquiry, this study investigates the attributes (i.e., the necessary and sufficient conditions) of good ecosystem-based plans, and then explores and interprets these attributes using hierarchy theory. What are the attributes of good ecosystem-based municipal plans? The Primary relationship under investigation is between ecosystem-based plans and their quality (i.e., their goodness). The central research question seeks a descriptive answer and is stated as follows: What are the attributes of good ecosystem-based municipal plans? The subsequent research question seeks explanative content and is stated as follows: How can hierarchy theory be used to explore and interpret the attributes of good ecosystem-based municipal plans? In order to address these two questions, the research process consists of four general phases. First, after a comprehensive and systematic literature review, a tentative plan evaluation framework for ecosystem-based municipal plans is posited. Second, the Delphi survey technique is employed to build on the tentative evaluation framework in order to determine which plan form, plan content and planning process conditions are necessary and sufficient for the evaluation of ecosystem-based plan quality. In the Delphi survey design, individual response stability testing is undertaken before level of consensus criteria are applied. Third, the results of the Delphi exercise are then critically examined in terms of meta-criteria analysis. Fourth, the research results are explored and interpreted by employing hierarchy theory, and then made operational for subsequent field work. The primary results of the research include the following: (1) Contribution to methodology. A methodologically-grounded and theoretically-oriented evaluation instrument suitable for judging the quality of ecosystem-based municipal plans is derived; (2) Contribution to theory. Hierarchy theory is synthesized into a framework of objects and implications suitable for applicability to ecosystem-based planning. In other words, the applicability of hierarchy theory is extended to include ecosystem-based planning, and ecosystem-based planning is simultaneously grounded in theory; and, (3) Contribution to identification of needed research directions. Potential directions for future research are recorded throughout the investigation.
Keywords: Environmental Sciences.